Sexual size dimorphism in Black-Browed Albatross (Diomedea melanophris) incidentally killed during longline operations - Gandini, Patricia Alejandra (2009)
Black-Browed Albatross (Diomedea melanophris) displays little sexual dimorphism and although males are usually larger than females, sexing birds by direct observation is difficult. We evaluated sexual size dimorphism in this species and provided a reliable method to predict the sex of measured birds. Discriminant Analysis of six morphometric measurements of adult birds indicated that only three variables (bill depth, head width and nape) were the most accurate variables to use in a discriminant function model, predicting sex with 87% of reliability.